Prognostic Value of Exercise Capacity in Kidney Transplant Candidates - Sean Tan; Yi Wen Thang; William R. Mulley; Kevan R. Polkinghorne; Satish Ramkumar; Kevin Cheng; Jasmine Chan; John Galligan; Mark Nolan; Adam J. Brown; Stuart Moir; James D. Cameron; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Exercise stress testing for cardiovascular assessment in kidney transplant candidates has been shown to be a feasible alternative to pharmacologic methods. Exercise stress testing allows the additional assessment of exercise capacity, which may have prognostic value for long‐term cardiovascular outcomes in pre‐transplant recipients. This study aimed to evaluate the prognostic value of exercise capacity on long‐term cardiovascular outcomes in kidney transplant candidates. Methods and Results We retrospectively evaluated exercise capacity in 898 consecutive kidney transplant candidates between 2013 and 2020 who underwent symptom‐limited exercise stress echocardiography for pre‐transplant cardiovascular assessment. Exercise capacity was measured by age‐ and sex‐predicted metabolic equivalents (METs). The primary outcome was incident major adverse cardiovascular events, defined as cardiac death, non‐fatal myocardial infarction, and stroke. Cox proportional hazard multivariable modeling was performed to define major adverse cardiovascular events predictors with transplantation treated as a time‐varying covariate. A total of 429 patients (48%) achieved predicted METs. During follow‐up, 93 (10%) developed major adverse cardiovascular events and 525 (58%) underwent transplantation. Achievement of predicted METs was independently associated with reduced major adverse cardiovascular events (hazard ratio [HR] 0.49; [95% CI 0.29–0.82], P=0.007), as was transplantation (HR, 0.52; [95% CI 0.30–0.91], P=0.02). Patients achieving predicted METs on pre‐transplant exercise stress echocardiography had favorable outcomes that were independent (HR, 0.78; [95% CI 0.32–1.92], P=0.59) and of similar magnitude to subsequent transplantation (HR, 0.97; [95% CI 0.42–2.25], P=0.95). Conclusions Achievement of predicted METs on pre‐transplant exercise stress echocardiography confers excellent prognosis independent of and of similar magnitude to subsequent kidney transplantation. Future studies should assess the benefit on exercise training in this population.